Management of osteoarthritis at the base of the thumb: a multicentre service evaluation project. (May 2020) - Parker, Simon; Riley, Nicholas; Dean, Benjamin; ,
Abstract : Aims: Base of thumb osteoarthritis (BTOA) is a common age-related disease which has a significant negative impact upon quality of life. Our aim was to assess current UK practice in secondary care with regard to the nature of non-surgical treatments, the surgical procedures most commonly performed, and factors influencing the surgical decision-making process. Methods: Ten consecutive patients undergoing surgery for BTOA between March 2017 and May 2019 were prospectively identified in 15 UK centres. Demographic details, duration of symptoms, radiological grade, non-surgical management strategies, and surgery conducted were recorded. A supplementary consultant questionnaire consisting of four multiple-choice-questions (MCQ) based on hypothetical clinical scenarios was distributed. Results: A total of 150 patients were identified with a mean age of 64 years (SD 9), comprising 119 females and 31 males. Median duration of symptoms prior to surgery was 24 months (Interquartile range (IQR) 12 to 40). Hand therapy was used in 67 patients (45%), splints in 80 (53%), and 121 patients (81%) received one or more intra-articular injections, of which 81 (67%) were image-guided (14 (12%) ultrasound and 67 (55%) fluoroscopic). Only 48 patients (32%) received all three non-surgical treatments. Simple trapeziectomy (79 patients) and trapeziectomy with ligament reconstruction and/or tendon interposition (69 patients) were the most commonly performed operations. One patient was treated with arthrodesis, and one with arthroplasty. The supplementary questionnaire revealed that no specific patient or disease characteristics significantly influenced the type of surgery undertaken. Conclusion: We found considerable variation in practice of both non-surgical and surgical management of BTOA. The proportion of patients exhausting non-surgical strategies before being offered surgery is low. Surgeons tend to favour a single type of surgery irrespective of patient or disease characteristics. Cite this article: Bone Joint J 2020;102-B(5):600–605.